2023
DOI: 10.3758/s13428-023-02087-4
|View full text |Cite
|
Sign up to set email alerts
|

The Empathy for Pain Stimuli System (EPSS): Development and preliminary validation

Abstract: We present the Empathy for Pain Stimuli System (EPSS): a large-scale database of stimuli for studying people’s empathy for pain. The EPSS comprises five sub-databases. First, the Empathy for Limb Pain Picture Database (EPSS-Limb) provides 68 painful and 68 non-painful limb pictures, exhibiting people’s limbs in painful and non-painful situations, respectively. Second, the Empathy for Face Pain Picture Database (EPSS-Face) provides 80 painful and 80 non-painful pictures of people’s faces being penetrated by a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
(53 reference statements)
0
5
0
Order By: Relevance
“…Previous studies have shown that: (i) the pain intensity rating scores of painful pictures were significantly higher than those of non-painful pictures; (ii) painful pictures induced significantly more negative feelings than non-painful pictures; (iii) painful pictures were significantly more exciting than non-painful pictures; (iv) painful pictures were rated as more out of control than non-painful stimuli ( Meng et al ., 2023 ). These results were also validated by the present study.…”
Section: Methodsmentioning
confidence: 98%
See 2 more Smart Citations
“…Previous studies have shown that: (i) the pain intensity rating scores of painful pictures were significantly higher than those of non-painful pictures; (ii) painful pictures induced significantly more negative feelings than non-painful pictures; (iii) painful pictures were significantly more exciting than non-painful pictures; (iv) painful pictures were rated as more out of control than non-painful stimuli ( Meng et al ., 2023 ). These results were also validated by the present study.…”
Section: Methodsmentioning
confidence: 98%
“…A total of 136 pictures, consisting of 68 painful and 68 non-painful pictures, from the Empathy for Limb Pain Picture Database (EPSS-Limb) ( Meng et al ., 2023 ), were selected and used in the current study. The picture database has previously been validated and used in published studies ( Meng et al ., 2019 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first block was a short training block (6 trails) with a different set of pictures (Canizales et al, 2013 ) but with similar instructions as in the subsequent two blocks. In the second and the third block, participants viewed 96 pictures of hands (48 trials per block; Meng et al, 2012 ; Meng et al, 2023 ; Figure 1 ) and were asked to decide if a picture was painful (press right “Ctrl” button) or non-painful (press left “Ctrl” button), while their EEG responses were recorded. In the last and fourth block, measuring behavioral pain ratings but no EEG, the participants viewed the same 48 pictures, but this time they were asked to rate them on a 1–6 scale (1 = no pain; 6 = very intensive pain).…”
Section: Methodsmentioning
confidence: 99%
“…
Figure 1. Example of stimuli used in the task (Meng et al, 2012; Meng et al, 2023 ) (A and B); example of an EEG trial in the pain judgment task (C).
…”
Section: Methodsmentioning
confidence: 99%